PENGARUH PEMBERIAN BEBERAPA JENIS GULA DAN SUMBER NITROGEN TERHADAP PRODUKSI NATA DE PINA - Yusmarini '; Usman pato; Vonny Setiaries Johan (Universitas Riau, 2004)
The effect of addition of various sugars and nitrogen sou rces on the production of nata de pina was evaluated.Data obtained were treated by the analysis of variance followed by Duncan's New Multiple Range Ttest Resultsof study indicate that various sugars and nitrogen sources significiintly affected the thickness, weight andrcndcmcnt of nata, however no effect of these compounds on the water content. Combination of sucrose assource of sugar and urea as source of nitrogen exhibited the highest production of nuta compared to othertreatments.